CD5 expression in marginal zone lymphoma predicts differential response to rituximab or bendamustine/rituximab. Issue 1 (2nd January 2022) - Hsu, Andrew; Kurt, Habibe; Zayac, Adam S.; Olszewski, Adam J.
Abstract: We examined outcomes of 244 patients with marginal zone lymphoma (MZL) diagnosed in 2010–2020, of which 25 (10%) expressed CD5. CD5 expression was present in 22% of splenic, 8% of nodal, and 5% of extranodal MZL, and showed frequent blood/bone marrow involvement, elevated lactate dehydrogenase, and TP53 deletions. CD5 expression was not associated with progression-free or overall survival, but it conferred a significantly higher risk of histologic transformation (22% versus 4% at 5 years, p  = 0.002). Among patients receiving first-line rituximab monotherapy, CD5 expression was associated with lower response rate (30% versus 77%, p  = 0.006), PFS (25% versus 45% at 3 years, p  = 0.003) and OS (44% versus 77%, p  = 0.010), whereas CD5 status did not significantly affect outcomes of patients receiving bendamustine with rituximab ( P for interaction = 0.012 for progression-free survival). CD5-positive MZL may have a propensity to leukemic dissemination, histologic transformation, and may derive benefit from first-line bendamustine/rituximab rather than rituximab alone.